Employees’ behaviour on smoke-free policy - Abdul Manan, Kamaruzzaman; Ahmad, Che Mahzan (IIUM Press, International Islamic University Malaysia, 2017)
This book contributes towards the body of knowledge in addressing smoking as one of the problems of the employees. This idea corresponds with the suggestions that are mentioned by Antero, Maritta, Erkki and Kari (2001) whereby in order to go forward in achieving the smoke-free workplace objectives, more research should be conducted to understand the actual conditions of employee’s problems, attitudes and life patterns. Smoking is one of the avoidable problems faced by Malaysian societies (Lee & Tam, 2014). However, there is still scarcity of studies from the Malaysian tobacco consumption perspectives. This book measures the extent of employees’ knowledge, attitude and behaviour of the smoke-free policy and will enhance the understanding of tobacco cessation issues from the employee’s perspective.